One last stop - McQuiston, Casey (St. Martin's Griffin, 2021)
"From the New York Times bestselling author of Red, White & Royal Blue comes a new romantic comedy that will stop readers in their tracks... "Dreamy, other worldly, smart, swoony, thoughtful, hilarious - all in all, exactly what you'd expect from Casey McQuiston!" - Jasmine Guillory, New York Times bestselling author of The Proposal and Party for Two. Cynical twenty-three-year old August doesn't believe in much. She doesn't believe in psychics, or easily forged friendships, or finding the kind of love they make movies about. And she certainly doesn't believe her ragtag band of new roommates, her night shifts at a 24-hour pancake diner, or her daily subway commute full of electrical outages are going to change that. But then, there's Jane. Beautiful, impossible Jane. All hard edges with a soft smile and swoopy hair and saving August's day when she needed it most. The person August looks forward to seeing on the train every day. The one who makes her forget about the cities she lived in that never seemed to fit, and her fear of what happens when she finally graduates, and even her cold-case obsessed mother who won't quite let her go. And when August realizes her subway crush is impossible in more ways than one-namely, displaced in time from the 1970s-she thinks maybe it's time to start believing. Casey McQuiston's One Last Stop is a sexy, big-hearted romance where the impossible becomes possible as August does everything in her power to save the girl lost in time"--